LINGUISTIC ANALYSIS OF ARABIC ARTICLES IN MAHMUD AZ-ZAMKHSHARI'S WORK "AL-MUSTAQSA FI AMSAL AL-ARAB" - Niyazaliyeva Munira Rustam qizi (International Journal of Literature and Language Studies, 2026)
This article provides a linguistic analysis of Mahmud az-Zamakhshari’s work “Al-Mustaqsa fi amsal al-Arab.” The structure of the treatise, the semantic and structural features of Arabic proverbs, and a comparative analysis of Arabic and Uzbek proverbs are examined. The article demonstrates that Zamakhshari’s analytical method — combining lexical, historical, and grammatical analysis — remains relevant for contemporary comparative paremiology and linguoculturology.